Daugiareiškmiškumo dekodavimas grožiniame tekste - Genienė, Izolda (Kalbotyra, 1998)
Polysemy requires a different treatment in language than it does in speech. The sense of the word in literature is dependent both on the objective (linguistic and stylistic context) and on the subjective context including the readers’ experience and the influence of the surrounding world. On a purely linguistic and stylistic level the polysemy of the word in the language is to be taken into account. The more polysemantic a word is in the language, the more senses it can generate in the contexts of decoding. The potential senses in the text can be ‘roused to life’ with a plurality of meanings depending upon the readers’ context. The decoding of a text becomes productive when the meanings of the linguistic and stylistic contexts are coupled with selective approaches and methods of literary theory.